Coping with Young Delinquents in Naples: an Approach in Clinical Sociology (between Foucault and Marcuse) - Corsale, Massimo (International Journal of Criminology and Sociology, 2013)
Young delinquents in Italy are seldom convicted in jail: in the most cases they stay within little communities (less than ten guests) where social workers give them some educational opportunities. The paper is concerned with some experiences made with such boys, aiming to put them in a situation where they could try a different relation with rules: they usually come indeed from a social marginal environment, where rules (namely the ones accepted in central society and enforced by law) are generally refused; here two experiences are examined: a regular job within a big manufactory (electrical household appliances), as well as a practical sailing course with participation to a big final regatta, where the boys have had a positive relation with rules, namely the ones necessary to achieve the goals connected with the experience. From a theoretical point of view, such experiences could give a new perspective on the classical concept of “discipline” proposed by Foucault, putting it in relation with the Marcuse’s theory of “necessary/additional repression”.